Christianity’s Last Stand: Visions of Spirituality in Post-1970 African American Women’s Literature - Harris, Trudier (Religions, 2020)
Christianity appealed to writers of African descent from the moment they set foot on New World soil. That attraction, perhaps as a result of the professed mission of slaveholders to “Christianize the heathen African,” held sway in African American letters well into the twentieth century. While African American male writers joined their female counterparts in expressing an attraction to Christianity, black women writers, beginning in the mid-twentieth century, consistently began to express doubts about the assumed altruistic nature of a religion that had been used as justification for enslaving their ancestors. Lorraine Hansberry’s Beneatha Younger in A Raisin in the Sun (1959) initiated a questioning mode in relation to Christianity that continues into the present day. It was especially after 1970 that black women writers turned their attention to other ways of knowing, other kinds of spirituality, other ways of being in the world. Consequently, they enable their characters to find divinity within themselves or within communities of extra-natural individuals of which they are a part, such as vampires. As this questioning and re-conceptualization of spirituality and divinity continue into the twenty-first century, African American women writers make it clear that their characters, in pushing against traditional renderings of religion and spirituality, envision worlds that their contemporary historical counterparts cannot begin to imagine.